Energy Efficiency of the Carbonate Hydroxyapatite Nanoparticle Synthesis Using Microwave Heating Treatment and Its Effect on Material Characteristics - Saifuddin Aziz; Harno Dwi Pranowo; Ika Dewi Ana; Yusril Yusuf (Universitas Gadjah Mada, 2024)
This work aimed to study the energy efficiency of the synthesis process of carbonated hydroxyapatite (CHA) nanoparticles using microwave heating treatment and its effect on material characteristics. Microwaves can provide heat quickly, so it is expected to increase the efficiency of CHA synthesis through the heat provided. The CHA nanoparticles were synthesized using precipitation and heated using a microwave oven. The unheated and hydrothermal-heated precipitation methods were also conducted for comparison purposes. The microwave-heated precipitations were done at 270 W for 0.05, 0.10, and 0.15 h, while the hydrothermal-heated precipitations were done at 100 °C for 1, 2, and 3 h. The CHA materials were characterized using an infrared spectrophotometer, X-ray diffractometer, and electron microscope. The X-ray diffractogram and infrared spectra confirmed that the synthesized materials had a hydroxyapatite crystal phase with a CO32− functional group in their spectra. Microscopic images revealed that the materials were nanometer-sized grain aggregates. The heat treatment and duration increased the material characteristics, i.e., crystallinity, crystallite, and grain size. The CHA with microwave heat treatment had the highest crystallinity and crystallite size. The electrical energy calculation revealed microwave heating had better energy efficiency than hydrothermal heating.